2002
DOI: 10.1159/000063077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Consumption, Advanced Age and Overweight on the Physical Characteristics of Cholesterol Gallstones and Biliary Lipid Composition in West Algerian Women

Abstract: The aim of this study was to determine the effect of age, overweight and food consumption on the number and size of cholesterol stones and bile composition in west Algerian women undergoing surgery for cholelithiasis. Patients were divided into four groups according to body mass index (BMI, weight/height2, kg/m2) and age. The highest number of patients with cholesterol gallstones was observed in the older women, in particular in those being overweight. In all patients, the stone number an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The latter factors are induced by chronic overweight, promoting GSD through their respective mechanisms, while the inverse correlation between BMI and GSD may result from the above stronger confounding factors, which could interfere with the effect of BMI on GSD formation. In addition, overweight might not only impair biliary lipid composition, diminishing cholesterol saturation index to increase the incidence of cholesterol gallstones [45], but also reduce leptin to decrease gallbladder contractility [28]. Therefore, the formation of gallbladder stones is enhanced by the imbalance between the amounts of total cholesterol, bile acids and lecithin, in combination with the abovementioned factors in chronic overweight before obesity [46], corroborating the present results.…”
Section: Discussionsupporting
confidence: 86%
“…The latter factors are induced by chronic overweight, promoting GSD through their respective mechanisms, while the inverse correlation between BMI and GSD may result from the above stronger confounding factors, which could interfere with the effect of BMI on GSD formation. In addition, overweight might not only impair biliary lipid composition, diminishing cholesterol saturation index to increase the incidence of cholesterol gallstones [45], but also reduce leptin to decrease gallbladder contractility [28]. Therefore, the formation of gallbladder stones is enhanced by the imbalance between the amounts of total cholesterol, bile acids and lecithin, in combination with the abovementioned factors in chronic overweight before obesity [46], corroborating the present results.…”
Section: Discussionsupporting
confidence: 86%
“…Ramadan diurnal intermittent fasting (RDIF) may be one of the most extensively studied types of religious fasting [30, 31], with a vast number of original research, system-atic reviews and meta-analyses demonstrating that RDIF is associated with variable changes in body weight [32][33][34], body composition [33, 35-37] and fat mass [38,39], with an emphasis on visceral fat [40], serum lipids [34,41,42], immunomodulatory responses [43][44][45][46][47], and inlammatory and oxidative stress changes [46,[48][49][50][51][52][53]. Furthermore, some Azizi [7] reported that RDIF yielded changes in body weight that varied between individuals, ranging from weight gain to weight loss, depending on total caloric intake during the fasting night hours in comparison to the pre-fasting intakes [7].…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis for body weight change was performed to investigate diferences between countries. We :Co de [42] cant changes in body weight over Ramadan 22 16 Norouzy et al [128] Iran achieved this subgroup analysis if three or more studies were available from any given country.…”
Section: Main Outcomes and Measuresmentioning
confidence: 99%
“…Subsequently, hepatic cholesterol biosynthesis is increased, giving a theoretical potential to therapy with cholesterol-lowering agents [9]. Increased hepatic cholesterol synthesis results in a rise of bile cholesterol-saturation index that is proportional to BMI but independent of other variables such as ethnicity, gender, or age [10]. Morbidly obese individuals have also been shown to have increased levels of mucin within the gallbladder, which accelerates the growth of cholesterol monohydrate crystals into gallstones.…”
Section: Opinion Statementmentioning
confidence: 99%